2009
DOI: 10.1111/j.1471-0528.2009.02182.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy following obstetric fistula repair, the management of delivery

Abstract: Obstetric fistula patients invariably have dreadful obstetric histories. The antecedent delivery usually ends in a stillbirth and even multiparous obstetric fistula patients often have previous histories of multiple stillbirths and neonatal deaths. There is very little published on subsequent pregnancies following obstetric fistula repair or even on reproductive capabilities after repair. This study examines 49 pregnancies following obstetric fistula repair and the management and outcome of delivery.Keywords C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 4 publications
1
21
2
Order By: Relevance
“…Though 40% of the entire study population had no living child, the number of living children was higher as expected in the women with subsequent childbirth after obstetric fistula. Childless women are more likely to be divorced by their husbands as a result of their disorder, than women with living children and so it would appear that the presence of children can mediate the physical stress that threatens to overwhelm the coping abilities of the parent [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though 40% of the entire study population had no living child, the number of living children was higher as expected in the women with subsequent childbirth after obstetric fistula. Childless women are more likely to be divorced by their husbands as a result of their disorder, than women with living children and so it would appear that the presence of children can mediate the physical stress that threatens to overwhelm the coping abilities of the parent [6].…”
Section: Discussionmentioning
confidence: 99%
“…A study from northern Nigeria conducted among women with successful repair of fistula suggested an increase in the mean fetal birth weight and reduced incidence of low birth weight. Some related studies have demonstrated that though vaginal delivery is possible in women with successfully repaired fistula, the maternal and fetal outcomes are unfavourable and thus elective Caesarean section provides better outcomes [6,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 While several researchers have indicated that the optimal mode of delivery after the successful repair of an obstetric fistula is an elective Caesarean section, the evidence for this approach is limited. 7,8 However, among women with successfullyrepaired obstetric fistulae who were allowed to deliver vaginally, 55% had their fistulae opened during delivery. 9 In the current case, the patient became pregnant twice and successfully delivered both times via elective Caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Sir, From my experience in Zaria, northern Nigeria, I agree with Dr Browning 1 that the provision of a hostel adjacent to maternity units is essential as part of the antenatal care of women with previous vesicovaginal fistula (VVF) repair. In Zaria, only a small minority of the pregnant women who had VVF in a previous pregnancy used the available hostel when they needed it.…”
mentioning
confidence: 93%